A Pragmatic Study Of BBC and CNN Economic News - Hameed Aubdlatif, Hussein; Izzat Salman, Anees (International Journal of Psychosocial Rehabilitation, 2020)
The present study is an attempt to check and analyze the BBC and CNN economic news from a pragmatic perspective. The study aims at achieving the following two principal objectives. The first one is to talk about and make sense of discourse act hypothesis just as its different sorts, while the second one is to test discourse acts ideas and apply them to monetary news inside chief activity. It is noted that discourse acts assume a significant task in the field of talk examination and are the most significant guideline and standard for a book, which is clear when deciphering a particular talk text (found in one sentence or gathering of sentences). The present analysis is tied in with utilizing various sorts of discourse demonstration in chosen English monetary news. They were picked arbitrarily that from News channels BBC and CNN. The issue that the analyst bargains inside this paper is to distinguish the various kinds of discourse in the monetary content and afterward comprehend why some discourse demonstrations are worked more than others. The examination was meant to contemplate discourse acts in the chosen English financial news for five writings. The theoretical structure of the investigation was examined monetary news to accomplish consequences of discourse acts in the news that would be referenced later. The current paper falls into two parts and an end. However, the study will adopt notions taken from Grice’s cooperative principles (1995), Austin speech act theory (1962), and Searle’s speech act theory (1969) as its model since their notions are relative to the aims of the present study.